2018
DOI: 10.1007/s10886-018-1007-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Milkweed Induced Defense on Parasite Resistance in Monarch Butterflies, Danaus plexippus

Abstract: Many plants express induced defenses against herbivores through increasing the production of toxic secondary chemicals following damage. Phytochemical induction can directly or indirectly affect other organisms within the community. In tri-trophic systems, increased concentrations of plant toxins could be detrimental to plants if herbivores can sequester these toxins as protective chemicals for themselves. Thus, through trophic interactions, induction can lead to either positive or negative effects on plant fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Although monarchs benefit from sequestration of milkweed cardenolides since they confer some level of protection against higher trophic levels 55 , 56 and infection 57 , at high levels these toxins negatively affect larval growth and survival 23 , 29 , 31 , 55 . To start examining if sequestration-associated exposure to cardenolides may also affect adult energy expenditure, we extracted and quantified cardenolide content of wings from adult specimens used in the respirometry trials.…”
Section: Resultsmentioning
confidence: 99%
“…Although monarchs benefit from sequestration of milkweed cardenolides since they confer some level of protection against higher trophic levels 55 , 56 and infection 57 , at high levels these toxins negatively affect larval growth and survival 23 , 29 , 31 , 55 . To start examining if sequestration-associated exposure to cardenolides may also affect adult energy expenditure, we extracted and quantified cardenolide content of wings from adult specimens used in the respirometry trials.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in cardenolide concentrations between these milkweed species are well-established in the literature, with swamp milkweed having consistently low cardenolides and tropical having consistently high. Common milkweed shows more variability, but consistently falls between this range [51][52][53][54]. We again examined monarch development and survival to the adult stage and tested grip strength [55] as an indicator of physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…While parasite replication occurs during the larval and pupal stages, disease symptoms are expressed during the adult stage and include reduced emergence success, body mass, mating ability, flight ability and lifespan (Bradley & Altizer, ; de Roode, Gold, & Altizer, ; de Roode, Yates, & Altizer, ), with greater parasite loads resulting in greater fitness losses (de Roode et al, ; de Roode, Yates, et al, ). Interestingly, previous studies showed that larvae feeding on milkweeds with greater concentrations of cardenolides result in lower parasite infection, growth and virulence (Gowler, Leon, Hunter, & de Roode, ; Lefèvre, Oliver, Hunter, & de Roode, ; de Roode, Pedersen, et al, ; de Roode, Rarick, Mongue, Gerardo, & Hunter, ; Sternberg et al, ; Sternberg, de Roode, & Hunter, ; Tan, Tao, Hoang, Hunter, & de Roode, ; Tao, Gowler, Ahmad, Hunter, & de Roode, ; Tao, Hoang, et al, ). At present, however, it remains unclear how cardenolides, parasites and the monarch's immune system interact.…”
Section: Introductionmentioning
confidence: 99%